Modeling and comparative analysis of packing of the polyfractional mixture of B[4]C powder; IOP Conference Series: Materials Science and Engineering; Vol. 116 : Advanced Materials and New Technologies in Modern Materials Science - Dvilis E. S. Edgar Sergeevich; Khasanov O. L. Oleg Leonidovich; Khasanov A. O. Aleksey Olegovich; Petyukevich M. S. Mariya Stanislavovna; Iazykov D. K. (2016, 2016)
Title screen